Excess Molar Volume of Binary Mixtures of Tetrachloroethylene + Acetylacetone, + Acrylonitrile, + Anisole and + Tetrahydrofuran at 303.15 K - Tripathi, Atri Deo; Agrawal, Meenu (Journal of Applied Solution Chemistry and Modeling, 2014)
Excess molar volumes have been measured by means of a dilatometer for tetrachloroethylene (TCE) +acetyl acetone, + acrylonitrile, +anisole and+ tetrahydrofuran at 303.15 K. VEm values are positive over the entire range of composition for TCE- anisole and TCE - acetyl acetone and negative for TCE- Tetrahydrofuran. For TCE - acrylontrile, VEm has been found to be negative up to x = 0.8379 and positive onward. Values of VmE for the various systems have been fitted by the method of least squares with smoothing equation, and have been discussed from the viewpoint of the existence of specific interactions between the components.